Air quality in the colombian andean region: behavior of tropospheric no2 from satellite data (2023)
This study focuses on the analysis of air quality behavior, with a specific focus on tropospheric nitrogen dioxide as a parameter of interest in the Andean region of Colombia. To achieve this analysis, 12 cities in the country were taken as reference points. By processing more than 250,000 images, crucial data were extracted to evaluate the behavior of air quality during the period between 2019 and 2022. The results reveal a counterintuitive behavior, as the city with the most inhabitants is not the one with the highest pollution levels.